The grain sorghum stem borer Chilo Partellus (Swinhoe) (Lepidoptera: Pyralidae) as pest on maize - Bate, Johanna Maria (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1989.